2004
DOI: 10.3354/meps279023
|View full text |Cite
|
Sign up to set email alerts
|

Role of TEP in the microbial food web structure. II. Influence on the ciliate community structure

Abstract: The structure of the bacterial population (free vs. attached bacteria), variations in bacterial abundance and ciliate group composition were monitored as a function of transparent exopolymeric particle (TEP) concentration during Phaeocystis globosa blooms that developed in mesocosms. Two ciliate groups dominated at different stages of the blooms. The oligotrichous ciliate Strombidium spp. were dominant during the growth phase of the blooms, when TEP volume concentration was lower than 20 ppm. The hypotrichous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…through an increase in the growth rates of diatoms that actively exude TEP precursors, particularly when nutrients become exhausted. Variations in microbial colonization of TEP have been explained by variability in the composition of TEP precursors, in degradability of TEP (Kepkay & Johnson 1988 and in grazing pressure (Mari et al 2004). In the present experiment, the increase in the rate of bacterial colonization of TEP appeared linked to the rapid formation of TEP after the diatom bloom in enriched turbulent tanks.…”
Section: Tep-heterotrophic Bacteria Interactionssupporting
confidence: 45%
“…through an increase in the growth rates of diatoms that actively exude TEP precursors, particularly when nutrients become exhausted. Variations in microbial colonization of TEP have been explained by variability in the composition of TEP precursors, in degradability of TEP (Kepkay & Johnson 1988 and in grazing pressure (Mari et al 2004). In the present experiment, the increase in the rate of bacterial colonization of TEP appeared linked to the rapid formation of TEP after the diatom bloom in enriched turbulent tanks.…”
Section: Tep-heterotrophic Bacteria Interactionssupporting
confidence: 45%
“…Consequently, dissolved organic matter leaches out of the marine snow, attracting not only chemotactic prokaryotes (Stocker et al 2008) but also their predators such as highly motile nanoflagellates (Fenchel & Blackburn 1999, Turk et al 2010. Bacterial grazing mortality can therefore exceed bacterial growth and colonization (Kiørboe et al 2004, Mari et al 2004. As marine snow ages, however, it becomes more refractory due to the intense utilization of easily degradable compounds (Müller-N iklas et al 1994, Turk et al 2010) and the production of refractory capsular material by marine-snow-attached bacteria (Heissenberger & Herndl 1994, Heissenberger et al 1996.…”
Section: Prokaryotic Activity Is Linked To Particle Developmental Stagementioning
confidence: 99%
“…Moreover, studies have indeed suggested that the reproduction rates of the dominant copepods can be limited by the docosahexaenoic acid (22:6 n-3, DHA) content of food algae during the summer season (see Evjemo et al 2008). Ciliates may consume minor fractions of heterotrophic bacteria (Lawrence & Snyder 1998, Mari et al 2004). This could mitigate P limitation, but it is an open question whether large herbi vorous ciliates (20 to 50 µm) are able to consume significant amounts of bacteria (linkage not represented in Fig.…”
Section: General Considerations Of the Nutrient Limitations Of Heteromentioning
confidence: 99%